Hubungan Status Sosial Ekonomi dengan Sindrom Metabolik Pada Pasien Rawat Jalan RSUD Labuang Baji Kota Makassar - Septiyanti Septiyanti; Nurhaedar Jafar; Hendrayati Hendrayati (Yayasan Citra Cendekia Celebes, 2020)
The increasing flow of globalization in all fields, technological and industrial developments have been many bring changes to people's behavior and lifestyle. Changes in food consumption patterns as well as reduced physical activity and environmental pollution also contribute to lifestyle changes. These changes have unconsciously influenced the epidemiological transition with the increasing cases of degenerative diseases. Along with these changes in human lifestyle, one of the problems that arise in the health sector is an increase in the incidence of metabolic syndrome. This study aims to determine the relationship of socioeconomic status with metabolic syndrome in outpatients at the Labuang Baji Makassar Hospital. This type of research is an analytic survey with a cross sectional approach. Sampling was done using accidental sampling technique with a sample size of 70 people. Data collection was carried out by collecting secondary data and primary data. Data analysis was performed using the chi-square test. The results showed that there was no significant relationship between socioeconomic status and metabolic syndrome. Metabolic syndrome patients were found to be highest at the age of 60-69 years. Most of the people with metabolic syndrome are women with retired jobs. The metabolic syndrome incidence increases with the high level of education.